Analysis of a Serious Adverse Reaction of Pulmonary Fibrosis Caused by Dronedarone - Yuyan Chen, PM; Zhendong Fu, MM; Xue Wen, MM; Mingxia Zhang, PM; Qiong Min, PM; Peng Wang, PM; Jin Zhang, MB; Jun Ren, PM; Wenbin Li, PD; Rong Wang, PD (Current Therapeutic Research, 2024)
Objective: This study aims to analyze a severe adverse reaction of pulmonary fibrosis induced by dronedarone hydrochloride tablets, and to provide a reference for clinical rational medication through drug precautions. Methods: A case of pulmonary fibrosis induced by dronedarone hydrochloride tablets, along with related literature was retrospectively analyzed. Results: Patients over 65 years old with a history of exposure to amiodarone may increase the incidence of pulmonary toxicity induced by dronedarone, and dronedarone should not be selected as a substitute treatment drug for patients with amiodarone-induced pulmonary toxicity. Conclusions: It is recommended that clinicians monitor the diffusion capacity of carbon monoxide and lung ventilation function of patients before and after using dronedarone for treatment. For patients with a history of amiodarone exposure, intermittent monitoring of chest X-rays and lung function is necessary. If lung function decreases, dronedarone should be immediately discontinued.